Carbon Aerogel as Electrode Material for Improved Direct Electron Transfer in Biosensors Incorporating Cellobiose Dehydrogenase. Issue 10 (6th October 2016) - Fort, Carmen Ioana; Ortiz, Roberto; Cotet, Liviu Cosmin; Danciu, Virginia; Popescu, Ionel Catalin; Gorton, Lo
Abstract: High mesoporous carbon aerogels (CA) were prepared by a sol‐gel method, followed by supercritical drying with liquid CO2 and pyrolysis under inert atmosphere. The morphological and structural characteristics (surface area, pore size distribution and pore volume) of CA were examined by using N2 adsorption/desorption isotherms, TEM, SEM and AFM measurements. CA, dispersed in a chitosan (Chi) solution, was immobilized on the surface of a glassy carbon (GC) electrode aiming to prepare an amperometric transducer able to improve the direct electron transfer (DET) between Phanerochaete chrysosporium cellobiose dehydrogenase ( Pc CDH) and the electrode. The resulting GC/CA‐Chi/ Pc CDH biosensor was optimized with regards to the loading of CA and Pc CDH, as well as pH of the buffer solution. The electroanalytical parameters of the optimized biosensor (maximum current responses (Imax ), apparent Michaelis‐Menten constants (KM )) were estimated from amperometric calibration curves for lactose. The remarkably high sensitivity towards lactose (133.7±0.2 µA cm −2 mM −1 ) at the GC/CA‐Chi/ Pc CDH electrode recommends the GC/CA‐Chi electrode as an efficient transducer for Pc CDH based biosensors, exploiting DET. Abstract :